Long-Term Mortality Rates in Acute De Novo Versus Acute-on-Chronic Heart Failure: From the Heart Function Assessment Registry Trial in Saudi Arabia. (October 2015) - AlHabib, Khalid F.; Kashour, Tarek; Elasfar, Abdelfatah A.; Alfaleh, Hussam; Hersi, Ahmad; Alshamiri, Mostafa; Alshaer, Fayez; Mimish, Layth; Almasood, Ali; AlHabeeb, Waleed; AlGhamdi, Saleh; Ghabashi, Abdullah; et al.
Aim: The heart function assessment registry trial in Saudi Arabia (HEARTS) is a national multicenter project that compared de novo versus acute-on-chronic heart failure (ACHF). Methods and Results: This is a prospective registry in 18 hospitals in Saudi Arabia between October 2009 and December 2010. The study enrolled 2610 patients: 940 (36%) de novo and 1670 (64%) ACHF. Patients with ACHF were significantly older (62.2 vs 60 years), less likely to be males (64% vs 69%) or smokers (31.6% vs 36.7%), and more likely to have history of diabetes mellitus (65.7% vs 61.3%), hypertension (74% vs 65%), and severe left ventricular dysfunction (52% vs 40%). The ACHF group had a higher adjusted 3-year mortality rate (hazard ratio, 1.6; 95% confidence interval [CI] 1.3-2.0; P < .001). Conclusion: Patients with ACHF had significantly higher long-term mortality rates than those with de novo acute heart failure (HF). Multidisciplinary HF disease management programs are highly needed for such high-risk populations.